The Influence of Short-Form Promotional Video Content on Movie Ticket Purchase Decisions Through Electronic Word of Mouth (E-WOM) Among Gen Z - Reysa Almaira Anandita; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
The development of social media has driven changes in promotional strategies in the film industry, particularly through the use of short video content such as TikTok, Instagram Reels, and YouTube Shorts. Short video content is considered capable of attracting audience attention, conveying information concisely, and encouraging interaction and digital conversation among users. In the context of Generation Z, electronic word of mouth (e-WoM) is an important factor that influences consumer confidence and decisions before purchasing movie tickets. This study aims to analyze the influence of short promotional video content on electronic word of mouth and movie ticket purchasing decisions, as well as to examine the role of e-WoM as a mediating variable. The study uses a quantitative approach with a causal design. Data were collected through an online questionnaire survey distributed to Generation Z who had seen short promotional video content and had watched movies in theaters. The sampling technique used was purposive sampling with a total of 90 respondents. The research instrument used a five-point Likert scale without neutral options. Data analysis was performed using linear regression analysis and mediation tests with the help of SPSS software.This study is expected to contribute academically to the development of digital consumer behavior studies, particularly regarding the role of short video content and electronic word of mouth in influencing movie ticket purchasing decisions. In addition, the results of this study are expected to provide practical considerations for film industry players in designing social media-based promotional strategies.